(untitled) (Journal of the Sylhet Agricultural University, 2025)
Tomato Yellow Leaf Curl Virus is very devastating pathogenic disease of tomato, which affect the yield and quality of tomato production in Bangladesh. Above mentioned experiment was conducted during summer season at Research Centre of Bangladesh Agricultural Research Institute, Joydebpur, Gazipur with a view to evaluating the yield and fruit quality parameters of Tomato Yellow Leaf Curl Virus resistant summer tomato in Gazipur condition. Variations in relation to yield and fruit quality characters were observed among the genotypes. Shelf life of different tomato lines ranged from 15.67 days to 18 days. The inbred line CLN-3862 exhibited longest shelf life (18.33 days) and lowest shelf life (15.67 days) was found in case of inbred line CLN-3735. The inbred line CLN-3791 showed highest yield potential (54.94 tha-1). On the other hand, the lowest yield obtained in the inbred line CLN-3859 which was 14.82 t/ha. In current study, only BARI Hybrid Tomato-8 exhibited highest Tomato yellow leaf curl virus (TYLCV) infection which was about 16.64% at 60 days after transplanting. Heart shape fruit was observed in the inbred line of CLN-3735, round shape fruit was observed in the inbred lines of CLN-3791, CLN-3850, CLN-3864, CLN-3906 and BARI Hybrid Tomato-8. Lengthened round shape fruit was observed in the inbred lines of CLN-3792, CLN-3849, CLN-3859, CLN-3860 and CLN3862. Flattened round shape fruit was observed in the inbred lines of CLN-3916. Among the genotypes, ripe fruit color of five tomato lines were light red color, three were yellowish red color, two were dark red color and two were orange color. Among the genotypes, blossom end shapes of eight were flat, two inbred lines had pointed and two had indented blossom end shape. In obtained results, fruit ridge of eleven were flat and only one was prominent and flesh color of four were light red, four were red, two were dark red and two were orange. Yield capacity and virus resistance of CLN-3792 exhibits the promicing results among all genotypes. J. Sylhet Agril. Univ. 11(1): 75-82, 2024